Physiologically based toxicokinetic modeling of inhaled ethyl tertiary- butyl ether in humans - Nihlen, A (Toxicological sciences, 1999)
A physiologically based toxicokinetic (PBTK) model was developed for evaluation of inhalation exposure in humans to the gasoline additive, ethyl tertiary-butyl ether (ETBE). PBTK models are useful tools to relate external exposure to internal doses and biological markers of exposure in humans. To describe the kinetics of ETBE, the following compartments were used: lungs (including arterial blood), liver, fat, rapidly perfused tissues, resting muscles, and working muscles. The same set of compartments and, in addition, a urinary excretion compartment were used for the metabolite tertiary-butyl alcohol (TBA). First order metabolism was assumed in the model, since linear kinetics has been shown experimentally in humans after inhalation exposure up to 50 ppm ETBE. Organ volumes and blood flows were calculated from individual body composition based on published equations, and tissue/blood partition coefficients were calculated from liquid/air partition coefficients and tissue composition. Estimates of individual metabolite parameters of 8 subjects were obtained by fitting the PBTK model to experimental data from humans (5, 25, 50 ppm ETBE, 2-h exposure; Nihlén et al., Toxicol. Sci., 1998; 46, 1-10). The PBTK model was then used to predict levels of the biomarkers ETBE and TBA in blood, urine, and exhaled air after various scenarios, such as prolonged exposure, fluctuating exposure, and exposure during physical activity. In addition, the interindividual variability in biomarker levels was predicted, in the eight experimentally exposed subjects after a working week. According to the model, raising the work load from rest to heavy exercise increases all biomarker levels by approximately 2-fold at the end of the work shift, and by 3-fold the next morning. A small accumulation of all biomarkers was seen during one week of simulated exposure. Further predictions suggested that the interindividual variability in biomarker levels would be higher the next morning than at the end of the work shift, and higher for TBA than for ETBE. Monte Carlo simulations were used to describe fluctuating exposure scenarios. These simulations suggest that ETBE levels in blood and exhaled air at the end of the working day are highly sensitive to exposure fluctuations, whereas ETBE levels the next morning and TBA in urine and blood are less sensitive. Considering these simulations, data from the previous toxicokinetic study and practical issues, we suggest that TBA in urine is a suitable biomarker for exposure to ETBE and gasoline vapor.